2013
DOI: 10.1063/1.4794901
|View full text |Cite
|
Sign up to set email alerts
|

Post-fabrication, in situ laser reduction of graphene oxide devices

Abstract: We report on post-fabrication, in situ, laser induced reduction of graphene oxide (GO) field effect transistors. Our one-step method is efficient, fast, and elevates the conductivity of GO transistor channels by two orders of magnitude. Compared to other reduction techniques, it is facile and simple since it does not require any stringent experimental conditions. Most importantly, we show here that it can be applied for, in situ, post-fabrication reduction of GO devices without compromising any of its componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 31 publications
6
49
1
Order By: Relevance
“…It has been demonstrated that the carbon content bonded to oxygen is reduced by laser scribing, indicating that the majority of oxygen groups are removed and effective reduction takes place [14]. Fig.1a shows the reduction mechanism with removal of oxygen groups.…”
Section: Resultsmentioning
confidence: 96%
“…It has been demonstrated that the carbon content bonded to oxygen is reduced by laser scribing, indicating that the majority of oxygen groups are removed and effective reduction takes place [14]. Fig.1a shows the reduction mechanism with removal of oxygen groups.…”
Section: Resultsmentioning
confidence: 96%
“…The product of the reduction process, commonly referred to as reduced graphene oxide (rGO), is of moderate electrical performance when compared to graphene, mainly due to the presence of oxygen related defects in the graphene lattice induced during the exfoliation and reduction processes. The efficiency of reduction strongly varies on the method and process parameters but residual oxygen groups and defects are commonly observed [5]. Graphene oxide (GO) sheets dispersed in water can be photo thermally reduced to produce relatively thin graphene electrodes on flexible substrate (like PET), with promising thermo electrical properties for sensing purposes.…”
Section: Introductionmentioning
confidence: 99%
“…9 This observation is in contrast to the increase in carrier mobility and improvement in the lattice order observed upon laser treatment of GO under an inert atmosphere. 26 The present results conrm that laser irradiation of GO under an inert atmosphere does not induce any structural disorder and the presence of reactive dopant gas(es) combined with laser irradiation is the main reason for the observed doping effects.…”
Section: Resultsmentioning
confidence: 82%